2017
DOI: 10.1002/rra.3161
|View full text |Cite
|
Sign up to set email alerts
|

Site fidelity and movement of a small‐bodied fish species, the rainbow darter (Etheostoma caeruleum): Implications for environmental effects assessment

Abstract: Small-bodied fish species are commonly used for the assessment of environmental effects because they are short lived, abundant, and they mature early. Although they are generally considered to be less mobile than larger bodied species, relatively little is known about their movement patterns. In this study, we tagged 3,001 rainbow darters (Etheostoma caeruleum) (≤76 mm) in the upper Grand River of southern Ontario with visible implant alpha tags and elastomers in 3 riffles. Five hundred sixty-five fish were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 32 publications
(58 reference statements)
0
15
1
Order By: Relevance
“…This study showed robust evidence that P. irwinni , a small native darter, could move over considerable distance (>30 km) in certain parts of the Biobío catchment. This is a considerable difference with previous studies investigating movements of darters using mark–recapture, as they only detected movements of <1 km (Hicks & Servos, 2017; Roberts & Angermeier, 2007). Possibly the difficulty to carry out large‐scale monitoring using mark–recapture made the detection of these movements.…”
Section: Discussioncontrasting
confidence: 80%
“…This study showed robust evidence that P. irwinni , a small native darter, could move over considerable distance (>30 km) in certain parts of the Biobío catchment. This is a considerable difference with previous studies investigating movements of darters using mark–recapture, as they only detected movements of <1 km (Hicks & Servos, 2017; Roberts & Angermeier, 2007). Possibly the difficulty to carry out large‐scale monitoring using mark–recapture made the detection of these movements.…”
Section: Discussioncontrasting
confidence: 80%
“…This distance was chosen because of the notable high site-fidelity exhibited byE. caeruleum individuals (Hicks & Servos, 2017). Candidate segments and sampling localities in both rivers were identified using freely available GIS data in combination with satellite imagery from Google Earth.…”
Section: Study Region and Sampling Methodsmentioning
confidence: 99%
“…Taking these factors together, the best explanation for the pattern observed is that life history of E. caeruleum , including high site fidelity and diet preferences of the species, shaped the spatial distribution of genetic diversity. Rainbow darters and their preferred prey have a preference for fast-moving riffle habitats and are less prevalent in deeper slow-moving pools (Hicks & Servos, 2017;Mueller et al, 2020). Therefore, the riffle-run-pool structure of streams may represent a permeable barrier to migratory movement further contributing to the observed pattern.…”
Section: Adherence To the Stream Hierarchy Modelmentioning
confidence: 99%
“…Three darter species, namely, rainbow darter (RBD, Etheostoma caeruleum), fantail darter (FTD, Etheostoma flabellare), and greenside darter (GSD, Etheostoma blennioides), each having slightly different life histories and ecological niches, were selected for this study. The RBD has been used as a sentinel species in many studies in the Grand River due to its small body size, high abundance, and small movement patterns, but few studies have contrasted the effects on other related darter species [4,23,37].…”
Section: Introductionmentioning
confidence: 99%